2016
DOI: 10.3389/fpsyg.2016.01285
|View full text |Cite
|
Sign up to set email alerts
|

The Exercise–Affect–Adherence Pathway: An Evolutionary Perspective

Abstract: The low rates of regular exercise and overall physical activity (PA) in the general population represent a significant public health challenge. Previous research suggests that, for many people, exercise leads to a negative affective response and, in turn, reduced likelihood of future exercise. The purpose of this paper is to examine this exercise–affect–adherence relationship from an evolutionary perspective. Specifically, we argue that low rates of physical exercise in the general population are a function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(89 citation statements)
references
References 87 publications
(104 reference statements)
7
73
1
8
Order By: Relevance
“…Therefore, BMEC could be conceived of as a reward. This assumption concurs with previous studies claiming that individuals possess an innate tendency to conserve energy and avoid unnecessary physical exertion [62,63], thereby explaining the negative affects experienced during exercise [13]. This evolutionary view of exercise may explain the exercise paradox: Why do individuals persist to be physically inactive despite knowledge of the risks associated with this inactivity?…”
Section: Behaviors Minimizing Energetic Cost As a Rewardsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, BMEC could be conceived of as a reward. This assumption concurs with previous studies claiming that individuals possess an innate tendency to conserve energy and avoid unnecessary physical exertion [62,63], thereby explaining the negative affects experienced during exercise [13]. This evolutionary view of exercise may explain the exercise paradox: Why do individuals persist to be physically inactive despite knowledge of the risks associated with this inactivity?…”
Section: Behaviors Minimizing Energetic Cost As a Rewardsupporting
confidence: 89%
“…This review showed a higher tendency to approach rather than avoid physical activity, irrespective of the individuals' level of exercise. While this result seems in line with the suggestion that physical activity is a reward, it does not discard the possibility that sedentary behaviors and cost minimization are also rewarding [62]. First, almost all studies relied on physically active (motivated) individuals, who are more likely to have repeatedly experienced positive affective experiences during exercise than physically inactive (unmotivated) individuals [13].…”
Section: Neurophysiological Studies Are Neededsupporting
confidence: 60%
“…Specifically, we hypothesized that in individual intending to be physically active, like all participants of the current study, sensory integration is shorter (i.e., larger positive deflection and earlier LRP onset latency) when they are asked to approach physical activity and avoid sedentary behaviors compared to approach sedentary behaviors and avoid physical activity (Hypothesis 2). Additionally, consistent with recent conceptual and review articles suggesting that individuals tend to save energy and avoid unnecessary physical exertion (Cheval, et al, 2018;Lee, Emerson, & Williams, 2016;Lieberman, 2015), lower reaction times when approaching physical activity and avoiding sedentary behaviors should require more cortical resources. Accordingly, we hypothesized higher attentional processing (larger P1 and late N1 amplitudes), conflict monitoring (larger early N1 and late N1 amplitudes), and inhibition (larger N2 amplitude) when approaching physical activity compared to sedentary behaviors and when avoiding sedentary behaviors compared to physical activity (Hypothesis 3).…”
Section: Introductionsupporting
confidence: 68%
“…The metabolic rate was shown to influence body size, resource use, rate of senescence and survival probability (Berghänel et al, 2015; Brown et al, 2004; DeLong et al, 2010; Munch and Salinas, 2009; Strotz et al, 2018; Voorhies and Ward, 1999). Preserving muscle effort may thus represent an essential pursuit for the brain (Baraduc et al, 2013; Bramble and Lieberman, 2004; Carrier et al, 2011; Cheval et al, 2018a, 2018b; Farshchiansadegh et al, 2016; Huang et al, 2012; Inzlicht et al, 2018; Kurzban et al, 2013; Lee et al, 2016; Lieberman, 2015; Mazzoni et al, 2007; Morel et al, 2017; Pageaux, 2016; Pageaux and Gaveau, 2016; Selinger et al, 2015; Shadmehr et al, 2016; Walton et al, 2006; Wang and Dounskaia, 2012).…”
Section: Discussionmentioning
confidence: 99%